LGBTQI* People in Germany Face Staggering Health Disparities - David Kasprowski; Mirjam Fischer; Xiao Chen; Lisa de Vries; Martin Kroh; Simon Kühne; David Richter; Zaza Zindel (DIW Weekly Report, 2021)
Discrimination and rejection experienced by LGBTQI* people affect their mental health and, in the long term, their physical health as well. Survey data from the Socio-Economic Panel and Bielefeld University show that LGBTQI* people in Germany are affected by negative mental health outcomes three to four times more often than the rest of the population. Poor physical health that may be stress-related, such as heart disease, migraines, asthma, and chronic back pain, are also far more common. A person's general well-being depends in part on their social environment. LGBTQI* people, and trans* people in particular, often feel lonely, which is cause for concern in view of increasing loneliness among most people during the coronavirus pandemic. The findings point to a marked health gradient, which should be addressed by measures including expanding queer safe spaces and by explicitly naming LGBTQI* hate crimes in the criminal code.
Keywords: J7; J15; J16; 330; LGBTQI*; trans*; mental health; health disparities; social networks; family ties; friendship ties